INVESTMENT OPPORTUNITY AND PERFORMANCE OF MANUFACTURING COMPANY IN INDONESIA - Saifi, Muhammad (Universitas Brawijaya, Indonesia, 2017)
This study aims to examine and explain the effect of Market to Book Value of Equity, Ratio of Depreciation to Firm Value, and Ratio of capital expenditure to book value of assets simultaneously to company performance are proxied by return on investment (ROI). In addition, this study also aims to determine the most dominant influence. The sample used in this study are 8 companies of Textile and Garment Sub-sector which go public in Indonesia Stock Exchange and got a total of 40 pooling data for period 2010-2014. This study uses the method of financial ratio analysis, descriptive statistical analysis, and inferential statistical analysis. The result of the study shows that the contribution of Market to Book Value of Equity, Ratio of Depreciation to Firm Value, and Ratio of capital expenditure to book value of assets simultaneously to company performance are proxied by return on investment (ROI) equal to 42.2%. Estimation results can be seen that the variable that has the largest standardization coefficient is the variable Market to Book Value of Equity. Thus, Market to Book Value of Equity has the most dominant influence on return on investment (ROI).